Sapos em ilhas: análise do efeito de isolamento sobre a morfologia de populações insulares de anfíbios do litoral do Rio de Janeiro. - Santos, Raoni Rebouças (2017)
This thesis is composed by three chapters about island anuran populations from Costa Verde, Southern coastal of Rio de Janeiro. The first chapter is about a record of physical anomalies in insular populations. Those presented much higher malformations incidence than mainland ones, which can highlight, among many possibilities, that there is a high inbreeding occurrence in those populations. The second chapter aims to verify if effect of nanism, already previously observed in insular populations, is reflected in life history of individuals. For this, were observed specimens ages associated to sexual characters’ emergence as indicators of sexual maturity, correlating to specimens’ size by island, in comparison to mainland populations. The third chapter extends the knowledge about size modification due to insularity in amphibians. In this, we pointed out that parameters placed by “island rule” probably need adjustment. Here we saw that species which according previous works would tend to nanism, do not present size reduction, or present gigantism, and two species of very small size presented nanism in islands.